2000
DOI: 10.1177/0011000000285006
|View full text |Cite
|
Sign up to set email alerts
|

Counseling Psychology’s Ambivalent Relationship with Master’s-Level Training

Abstract: Inspired by efforts by those who seek to redefine the practice of psychology as a master'slevel specialty, the authors examine counseling psychology's heightened ambivalence regarding master's-level training. First, they present a historical review of this issue. Next, they discuss current social and political pressures that, they suggest, have resulted in renewed tensions in the training of master's-level practitioners for the field of counseling psychology. They conclude with specific recommendations regardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Christenson and Jacobson (1994) suggested that we consider what training specific types of interventions require. Rather than provide extensive and general training, perhaps we need to consider what amount and kind of training is "good enough" to provide a specific treatment (McPherson, Pisecco, Elman, Crosbie-Burnett, & Sayger, 2000). In thinking about what training is necessary to develop skills in particular forms of intervention, we need also to think about how long a training period is required.…”
Section: Why Train In Clinicalmentioning
confidence: 99%
See 1 more Smart Citation
“…Christenson and Jacobson (1994) suggested that we consider what training specific types of interventions require. Rather than provide extensive and general training, perhaps we need to consider what amount and kind of training is "good enough" to provide a specific treatment (McPherson, Pisecco, Elman, Crosbie-Burnett, & Sayger, 2000). In thinking about what training is necessary to develop skills in particular forms of intervention, we need also to think about how long a training period is required.…”
Section: Why Train In Clinicalmentioning
confidence: 99%
“…Is this a reasonable suggestion, and if so, for what purpose would advanced training be necessary? McPherson et al (2000) implied that the basic value of postgraduate training is its bestowal of prestige. In the American context, they suggested that if masters-level trained practitioners obtain full licensure, this would "redefine the practice of psychology as a subdoctoral profession, establish an indifference to the distinctiveness of doctoral training for psychological practice, and devalue the scientist-practitioner training model" (P. 688).…”
Section: Why Train In Clinicalmentioning
confidence: 99%
“…2001, Hardwick & Jordan 2002, AACN 2005). However, core elements have been found that are not only generic to nursing but also to other Master’s programmes in the social and behavioural sciences, arts, engineering and education (Atkins & Redley 1998, Cervero 2000, McPherson et al. 2000Cabrera et al.…”
Section: Introductionmentioning
confidence: 99%
“…Contributing to the ambivalent relationship of counseling psychology to master's training, McPherson et al (2000) noted that in 1947, APA recommended the discontinuation of master's degrees for "lower level" psychological work. In contrast, however, in 1955 the APA Committee on Subdoctoral Education endorsed a two-year master's curriculum to address the surge of need for psychological services following World War II.…”
Section: Highlights Of Historical Contextmentioning
confidence: 99%